2013
DOI: 10.1039/c3ob40515j
|View full text |Cite
|
Sign up to set email alerts
|

Picomolar inhibition of cholera toxin by a pentavalent ganglioside GM1os-calix[5]arene

Abstract: Cholera toxin (CT), the causative agent of cholera, displays a pentavalent binding domain that targets the oligosaccharide of ganglioside GM1 (GM1os) on the periphery of human abdominal epithelial cells. Here, we report the first GM1os-based CT inhibitor that matches the valency of the CT binding domain (CTB). This pentavalent inhibitor contains five GM1os moieties linked to a calix[5]arene scaffold. When evaluated by an inhibition assay, it achieved a picomolar inhibition potency (IC50 = 450 pM) for CTB. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Later on, Marra et al [33] demonstrated that the copper-catalyzed azide–alkyne cycloaddition (CuAAC) [3435] at room temperature could afford divalent and tetravalent glycocalixarenes in very high yields and regioselectivity. Following these studies, a wide series of other examples appeared in the literature [18,3639] also exploiting the use of microwaves, ionic liquids and protected or even deprotected [17] saccharides. Usually, either the strategy of reacting an alkynylated-saccharide with a polyazide calixarene (dipolarophile-on-the-sugar) or an azido-sugar and a polyalkynocalixarene (dipolarophile-on-the-calix) work smoothly [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, Marra et al [33] demonstrated that the copper-catalyzed azide–alkyne cycloaddition (CuAAC) [3435] at room temperature could afford divalent and tetravalent glycocalixarenes in very high yields and regioselectivity. Following these studies, a wide series of other examples appeared in the literature [18,3639] also exploiting the use of microwaves, ionic liquids and protected or even deprotected [17] saccharides. Usually, either the strategy of reacting an alkynylated-saccharide with a polyazide calixarene (dipolarophile-on-the-sugar) or an azido-sugar and a polyalkynocalixarene (dipolarophile-on-the-calix) work smoothly [33].…”
Section: Resultsmentioning
confidence: 99%
“…Glycocalixarenes [912], calixarenes [13–15] adorned with carbohydrates at the upper and/or at the lower rims, have been demonstrated to be efficient multivalent ligands for a series of pathological lectins. For instance, cholera toxin is bound rather efficiently by calix[4]arene [16] and calix[5]arene [17] derivatives, while examples of Pseudomonas aeruginosa LecB binding were reported with galactosylcalixarenes blocked in different conformations [1819]. A few years ago we [2021] reported about the synthesis and inhibitory properties of a small library of lactosylthioureidocalixarenes and found that the cone derivatives I and III (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Lately the search has turned towards multivalent inhibitors 36 , e.g . using pentavalent GM1-os on different scaffolds, creating a 1:1 interaction of toxin and inhibitor 37, 38 . An interesting approach is to “let CT fight itself” using CTB modified with GM1-os residues as penta-GM1-os-CTB neoglycoprotein inhibitors 39 .…”
Section: Introductionmentioning
confidence: 99%
“…[5b, 6] Other recent studies have used GM1os ligands on both corannulene [7] and calixarene cores. [8] These pentavalent structures gave IC 50 values down to 5 nm and 450 pm, respectively. A pentameric carbohydrate core has also been used in the highly effective Starfish ligands for shiga-like toxin.…”
mentioning
confidence: 99%
“…[7,8] The ability of CTB to bind to a GM1-coated microtiter plate was assessed across a wide range of inhibitor concentrations. Pentavalent ligand W88E(GM1) exhibited an exceptionally low IC 50 value of 104 pm ( Figure 2 and Table 1), making it the most potent pentavalent ligand reported thus far.…”
mentioning
confidence: 99%